Asymptomatic cryptococcal antigenemia is associated with mortality among HIV‐positive patients in Indonesia - Ahmad Rizal Ganiem; Agnes Rengga Indrati; Rudi Wisaksana; Hinta Meijerink; Andre van derVen; Bachti Alisjahbana; Reinout vanCrevel (Journal of the International AIDS Society, 2014)
Introduction Previous studies, mostly from Africa, have shown that serum cryptococcal antigenemia may precede the development of cryptococcal meningitis and early death among patients with advanced HIV infection. We examined cryptococcal antigenemia as a risk factor for HIV‐associated mortality in Indonesia, which is experiencing a rapidly growing HIV epidemic. Methods We included ART‐naïve HIV patients with a CD4 cell count below 100 cells/μL and no signs of meningitis in an outpatient HIV clinic in Bandung, West Java, Indonesia. Baseline clinical data and follow‐up were retrieved from a prospective database, and cryptococcal antigen was measured in stored serum samples using a semiquantitative lateral flow assay. Cox regression analysis was used to identify factors related to mortality. Results Among 810 patients (median CD4 cell count 22), 58 (7.1%) had a positive cryptococcal antigen test with a median titre of 1:80 (range: 1:1 to 1:2560). Cryptococcal antigenemia at baseline was strongly associated with the development of cryptococcal meningitis and early death and loss to follow‐up. After one year, both death (22.4% vs. 11.6%; p=0.016; adjusted HR 2.19; 95% CI 1.78–4.06) and the combined endpoint of death or loss to follow‐up (67.2% vs. 40.4%; p<0.001; adjusted HR 1.57; 95% CI 1.12–2.20) were significantly higher among patients with a positive cryptococcal antigen test. Conclusions Cryptococcal antigenemia is common and clinically relevant among patients with advanced HIV in this setting. Routine screening for cryptococcal antigen followed by lumbar puncture and pre‐emptive antifungal treatment for those who are positive may help in reducing early mortality.